A New Species of Hylodes (Anura, Hylodidae) from Serra do Mar, Southeastern Brazil: The Fourth with Nuptial Thumb Tubercles - Malagoli, Leo R. [UNESP]; Sa, Fabio P. de [UNESP]; Canedo, Clarissa; Haddad, Celio F. B. [UNESP] (Herpetologists League, 2017)
Among the 25 Hylodes species described to date, only three species are known to have nuptial tubercles on the thumb, H. fredi, H. phyllodes, and H. pipilans. Careful analysis of the populations of these three species led us to discover a fourth, undescribed species from the Atlantic Forest of Serra do Mar in the State of Sao Paulo, southeastern Brazil. The new species exhibits light-colored, oblique lateral stripes and belongs to the Hylodes lateristrigatus group. The new species differs from its congeners by possessing the combination of three traits: (1) pointed nuptial tubercles, distributed in an elliptical area at the base of the dorsal surface of the thumb of males; (2) medium-sized; and (3) parameters of the advertisement call. Molecular analysis of a mitochondrial gene sequence (16S) strongly corroborates the description of phenotype by showing that the new species is genetically distinct from H. fredi, H. phyllodes, and H. pipilans. We also provide information on the natural history, behavior, and conservation status of the new species.
Keywords: Atlantic Forest; Brazilian torrent frogs; Hylodes phyllodes; Sympatry; Syntopy; Vocalization